An assessment of the potential of edible insect consumption in reducing human nutritional deficiencies in South Africa while considering food and nutrition security aspects. - Lategan, Anja (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScFoodSc)--Stellenbosch University, 2019.